Insulin in Myenteric Neurons: Time-Dependent and Regional Changes in Type 1 Diabetic Rats - Abigél Egyed-Kolumbán; Benita Onhausz; Bence Pál Barta; Zita Szalai; Ildikó Huliák; Mónika Kiricsi; Mária Bagyánszki; Nikolett Bódi (Cells)
Enteric neurons regulating motility display regional damage to diabetes. By inhibiting neuroinflammation, insulin can contribute to neuronal survival, therefore, we aimed to investigate the presence of insulin in myenteric neurons and their nitrergic population in acute and chronic rat models of type 1 diabetes. One or ten weeks after the onset of hyperglycemia, gut segments and the pancreas of control, diabetic, and insulin-treated diabetic rats were investigated. In the controls, insulin-immunoreactive neurons comprised 8–9% of the total myenteric neuronal population in the ileum and colon and 2–4% in the duodenum. Except for the duodenum, this proportion was significantly increased in acute hyperglycemic rats and was decreased in the colon of the chronic ones. However, the proportion of insulin-immunoreactive nitrergic neurons remained unchanged in all segments in chronic hyperglycemia. Immunogold electron microscopy revealed an increased density of insulin-labelling gold particles in diabetic duodenal ganglia of the chronic experiment. Insulin mRNA was not detected in intestinal samples either in controls or diabetics. These findings support time-dependent and regional alterations in the proportion of insulin-immunoreactive myenteric neurons and their nitrergic subpopulation. Regionally different insulin content of myenteric neurons may contribute to their protection from diabetic damage.